Archiving the political, narrating the personal - El Hajj, Sleiman (2019)
The year 2017 was the centenary of the controversial Balfour Declaration, and 2018 marked the seventieth year since the partitioning of Palestine and the historic Nakba prefiguring the creation of the State of Israel. These anniversaries occasioned several literary events in Lebanon—memoir launches, online biography releases, and the publication of interdisciplinary archival personal narratives. In addition, the literary timeline that extended toward the end of 2018 featured storytelling events rewriting, narrating, and (re)presenting transgender lives in Beirut, as well as an outpouring of feminist biographies, oral histories, and personal narratives, both by new and established woman writers...